Modern educational technologies: Pedagogy and Psychology - Danilchenko S. L., Mukambetova G. B., Kasymkulova U. D., Rakybaeva B. O., Glotova G. A., Belekova G. S., Kanaeva I. B., Glotova G. A., Kutbiddinova R. A., Frolova O. A., Ponikarovskaya V. V., Mychko E. I., Piatibratova I. V., Khotuliova O. V., Egorova G. V., Manasyrova E. M., Turdubaeva R. S., Vasileva I. S., Shvaikina N. S. (Modern educational technologies: Pedagogy and Psychology, 2024)
the chapter is devoted to the application of various methods and technologies in conducting integrated biology lessons at school. The idea of integrated learning involves achieving high-quality, high-quality, versatile education. The combination of knowledge in various subjects makes it possible for students to understand the essence of the subject and the practical meaning of complex concepts in various disciplines. The chapter offers various lesson options.
Keywords: инновационные технологии; интегрированное обучение; innovative technologies; естественно-научные дисциплины; integrated learning; natural sciences